Prognosis of synchronous colorectal carcinoma compared to solitary colorectal carcinoma: a matched pair analysis. Issue 12 (December 2019) - He, Wanbin; Zheng, Chengjun; Wang, Yonghong; Dan, Jie; Zhu, Mingjie; Wei, Mingtian; Wang, Jian; Wang, Ziqiang
Abstract : Background: Synchronous colorectal carcinoma (CRC) is a specific and rare type of colorectal malignancy. The data on the impact of synchronous CRC are controversial. This study aimed to compare the characteristics and prognosis between synchronous CRC and solitary CRC. Patients and methods: 252 patients who underwent surgery between October 2009 and June 2013 with synchronous CRC (n = 126) or solitary CRC (n = 126) were included. The patients were matched according to age, sex, American Society of Anesthesiologists score, BMI, cancer grade, tumor location, and tumor stage. The short-term outcomes included the length of hospital stay, complications, and 30-day mortality. Long-term endpoints were overall survival (OS), disease-free survival (DFS), and cancer-specific survival (CSS). Results: The median follow-up duration for all patients were 42.5 months. The incidence of synchronous CRC was high than in older and male patients as well as in mucinous adenocarcinoma containing signet-ring cell carcinoma, tumor deposit, and polypus. The length of hospital stay after surgery was longer for synchronous CRC than solitary CRC (median: 10 vs. 4 days, P = 0.033). In multivariate analysis, synchronous CRC was an independent prognostic factor associated with poor OS (hazard ratio: 2.355, 95% confidence interval: 1.322–4.195, P = 0.004), DFS (hazard ratio: 2.079, 95% confidence interval: 1.261–3.429, P = 0.004), and CSS (hazard ratio: 2.429, 95% confidence interval: 1.313–4.493, P = 0.005). Conclusion: The clinical and pathological features exhibit differences between synchronous CRC and solitary CRC and the prognosis of patients with synchronous CRC was poorer than those with solitary CRC.